2019
DOI: 10.1016/j.jvs.2018.12.037
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review and meta-analysis of bivalirudin application in peripheral endovascular procedures

Abstract: Objective: The direct thrombin inhibitor bivalirudin (BIV) was shown to be superior to unfractionated heparin (UFH) in percutaneous coronary interventions for reducing procedural blood loss. The aim of this study was to compare outcome profiles of BIV and UFH in peripheral endovascular procedures (PEPs) by synthesizing the currently available data. Methods: Following the PRISMA statement, we conducted a comprehensive literature search using Medline, Cochrane CENTRAL, PubMed, EMBASE, CINAHL Google scholar, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…reported no difference regarding major perioperative bleeding in patients undergoing peripheral endovascular procedures treated with BIV vs . UFH 30 . Compared with UFH, Omran et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported no difference regarding major perioperative bleeding in patients undergoing peripheral endovascular procedures treated with BIV vs . UFH 30 . Compared with UFH, Omran et al .…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al reported no difference regarding stroke events in patients undergoing peripheral endovascular procedures treated with BIV vs. UFH. 30 Differences between studies require more rigorous studies to confirm comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…23 A contemporary systematic review has analysed the efficacy of BIV versus UFH in peripheral endovascular interventions excluding intracardiac procedures. 24 Generally, patients who received BIV had significantly reduced risks of MACCE, net adverse clinical events, major and minor vascular complications, compared with the unfractionated UFH group. Patients who received BIV had a lower but non-significant odds of major bleeding (OR 0.72; 95% CI [0.47-1.11], minor bleeding (OR 0.74; 95% CI [0.55-1.00]) and transfusion.…”
Section: Other Direct Anticoagulantsmentioning
confidence: 85%
“…A heparinhatás felfüggesztésére protamin-szulfát használható, melynek alkalmazásakor súlyos reakciókat -úgymint hypotensio, bradycardia vagy anafilaxia -is leírtak, és melynek adásával kapcsolatban még kevesebb a konszenzus, mint a heparin használatával [27]. A heparinalkalmazás lehetséges alternatívája lehet a bivalirudinkezelés, amely a kimeneteli tényezők némelyikében előnyösebbnek bizonyult [41]. A gyógyszeres kezelés óvatos mérlegelése mellett a vérzést megelőző stratégiák további tényezői (behatolási hely választása, kompreszszió, érzáró eszközök) szintén fontosak [42], a perifériás intervenciók esetén is odafigyelést igényelnek.…”
Section: A Periprocedurális Gyógyszeres Kezelés Szempontjaiunclassified